Comparative Structural Study of Three Tetrahalophthalic Anhydrides: Recognition of X···O(anhydride) Halogen Bond and πh···O(anhydride) Interaction - Sergey V. Baykov; Artem V. Semenov; Eugene A. Katlenok; Anton A. Shetnev; Nadezhda A. Bokach (Molecules, 2021)
Structures of three tetrahalophthalic anhydrides (TXPA: halogen = Cl (TCPA), Br (TBPA), I (TIPA)) were studied by X-ray diffraction, and several types of halogen bonds (HaB) and lone pair···π-hole (lp···πh) contacts were revealed in their structures. HaBs involving the central oxygen atom of anhydride group (further X···O(anhydride) were recognized in the structures of TCPA and TBPA. In contrast, for the O(anhydride) atom of TIPA, only interactions with the π system (π-hole) of the anhydride ring (further lp(O)···πh) were observed. Computational studies by a number of theoretical methods (molecular electrostatic potentials, the quantum theory of atoms in molecules, the independent gradient model, natural bond orbital analyses, the electron density difference, and symmetry-adapted perturbation theory) demonstrated that the X···O(anhydride) contacts in TCPA and TBPA and lp(O)···πh in TIPA are caused by the packing effect. The supramolecular architecture of isostructural TCPA and TBPA was mainly affected by X···O(acyl) and X···X HaBs, and, for TIPA, the main contribution provided I···I HaBs.